Bactericidal Potentiality of Purified Terpenoid Extracts from the Selected Sea Weeds and its Mode of Action - Sumayya, Sabira Siraj; Lubaina, Abdulhadeef Shereefa; Murugan, Kumaraswamy (Journal of Tropical Life Science, 2020)
Terpenoids are hydrocarbons involved in a variety of basic functions in plants such as growth, developmentÂ and other physiological events. Terpenes and their associated molecules safe guard the organisms from pest, pathogen and herbivores. Similarly, therapeutically terpenoids function as antimicrobial agents against bacteria, fungi and viruses. The mechanism of bactericidal activities may be via inhibiting the synthesis of essential molecules like proteins, nucleic acids, cell-wall components, cell membrane derailment, bacterial DNA replication or inhibition of metabolic pathways. The crude methanolic extracts of the seaweeds were subjected to silica gel column chromatographic purification and eluted with different combinations of ethyl acetate: petroleum ether solvent systems. The eluted fractions were further subjected to thin layer chromatography and fractionated by GC-MS. The fractions obtained from Hypnea musciformis revealed the terpenoids such as eicosane, heneicosane, 2-pentadecnone, hexadecanoic acid methyl ester, n- hexadecanoic acid, hexadecanoic acid ethyl ester, heptadecanoic acid methyl ester, 11-octadecanoic acid metyl ester, whereas Kappapycus alvarezii Â displayed hexadecane, eicosane, heptadecane, octadecane, heneicosane, tricosane, hexadecanoic acid, methyl ester and beta amyrin. Similarly, Gracillaria dura revealed hexadecanoic acid methyl ester, n- hexadecanoic acid, 11-octadecanoic acid and phytol. Subsequently, the bactericidal activities of the purified terpenoid extracts from the sea weeds were carried. Initially, the extracts were tested for their in vitro antibacterial activity against six bacterial strains such as three Gram-positive (Staphylococcus aureus, Streptococcus mutans, Enterococcus faecalis) and three Gram-negative bacteria (Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa) by disc diffusion method. The results revealed that the purified terpenoid extracts of G. dura exhibited significant bactericidal potentiality against S. mutans as compared to other strains. The zone of inhibition, MIC and MBC values narrate the efficacy of the purified terpenoid extract of the species. Remarkable leaching of metabolites like protein and DNA further substantiates the MIC and MBC results. Scanning electron microscopic observations such as clumping, irregularity of cells and ballooned walls reflect the possible membrane damage accounted in the cells by the terpenoid extracts. Further studies are planned to validate the above data by using molecular tools.